Pendekatan Strategis dalam Menguatkan Spiritualitas Keagamaan Siswa - Arifin, Syamsul (Moderasi : Journal of Islamic Studies, 2024)
This study focuses on the strategies employed by Islamic Religious Education teachers at SMP Islam Bahrul Ulum Lumajang in fostering students' religious spirit through religious habituation and value-based teaching. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and documentation. Data analysis was conducted using Miles and Huberman's interactive analysis technique to identify key patterns in effective religious teaching strategies. The findings reveal that religious habituation practices, such as congregational prayers, Qur'an recitation sessions, and religious discussions, play a pivotal role in creating an environment conducive to students' spiritual development. The role of teachers as role models and mentors in building personal communication with students was also found to be highly significant in instilling religious values. These findings offer practical contributions to developing more interactive and experiential methods of religious education while enriching academic literature on Islamic religious education. The implications of this study underscore the importance of integrating religious habituation into the education system to shape students' spiritual character. Furthermore, the findings can serve as a guide for teachers, policymakers, and educational institutions in designing more adaptive and relevant religious education programs.